Satisfaction Analysis of The Establishment of a Website-Based Rank System Using Customer Satisfaction Index (CSI) And Importance Performance Analysis (IPA) Methods - Manurung, Asima; Siringoringo, Yan Batara Putra; Marpaung, J.L. (Sinkron : jurnal dan penelitian teknik informatika, 2024)
Promotion is one of the rights and obligations of lecturers for the performance burden that has been carried out by lecturers in order to implement the basic values of the Tri Dharma of Higher Education. The lecturer ranking system is implemented based on the lecturer's performance in teaching, research, and service that has been carried out. The lecturer rank system is implemented through a fairly long process and verification, so that the creation of a good ranking system will provide good added value in higher education services to the performance of lecturers for promotion. In this study, optimization of the lecturer's functional position promotion system will be carried out. The result achieved is a lecturer rating system by calculating the weight of credit scores in order to obtain a recommendation for promotion of lecturers for functional positions in universities and based on the Customer Satisfaction Index from a survey conducted on 50 respondents showing a score of 76.12%. It states that the rating system is at the level of satisfaction.